Influence of ultrashort laser drilling on magnetic and transport characteristics of HTS tapes. (6th June 2019) - Pokrovskii, S V; Mavritskii, O B; Egorov, A N; Mineev, N A; Timofeev, A A; Rudnev, I A
Abstract: We investigated the magnetic and transport characteristics of second generation high-temperature superconducting (HTS) tapes with an ordered array of antidots. We have performed modification of HTS GdBa2 Cu3 O7− δ industrial tape produced by SuperOx (Russia) using femtosecond laser exposure. We have created a local lattice of defects with the period 50 μ m and the size of every hole up to 1 μ m. We studied the dependence of the critical current on magnetic field and the angular dependence of the critical current. The influence of the array of artificial defects on the pinning force was shown in a wide range of magnetic fields. Transport and magnetization measurements reveal that these modifications of HTS tapes increases the trapped magnetic field and the critical current. The local increase in the critical current reaches 49%. These enhancements of the critical current have been observed in the intermediate angles. The proposed method of antidot arrays by laser drilling can be used for local modification of HTS tapes, and can improve the current-carrying characteristics of industrial tapes.